Thermoelectric Properties of Highly Ordered Metal-Organic Framework Films. (25th August 2016) - Chen, Xin; Wang, Zhengbang; Lin, Pengtao; Zhang, Kai; Baumgart, Helmut; Redel, Engelbert; Wöll, Christof
Abstract : In this work, quasi-liquid epitaxially highly oriented Surface Anchored Metal-Organic Framework (SURMOF) films and for comparison random polycrystalline MOF films loaded with tetracyano-quinodimethane (TCNQ) infiltration were fabricated and characterized. The horizontal Seebeck coefficient of the oriented SURMOF films and the random polycrystalline MOF films parallel to the sample surface was measured and has been discussed. The polycrystalline MOF films exhibit a high Seebeck coefficient of 949.9 µV/K at 290 K, while the horizontal Seebeck coefficient of oriented SURMOF films is practically around 0 µV/K. Because the quasi-epitaxial oriented SURMOF films are highly anisotropic, there is no measurable horizontal carrier transport parallel to the SURMOF surface. However in contrast to oriented SURMOF films, the electrical properties of random polycrystalline MOF films with sputtered Au contact pads could be measured. The high Seebeck coefficient of these random polycrystalline MOF films demonstrate a promising application potential of MOF films in future thermoelectric and electronic devices.